In Vitro Antimicrobial Activity of Copper Sulfate Pentahydrate Against Bacterial and Fungal Pathogens Associated with Vaginal Infections - Salih Mahdi Salih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
With growing antimicrobial resistance becoming a major health concern, there is an urgent need to explore alternative treatment options. This study examined the efficacy of copper sulfate pentahydrate (CSP) against eight microorganisms commonly implicated in vaginal infections. We tested three Candida species (C. albicans, C. glabrata, and C. tropicalis) along with five bacterial species, including Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Gardnerella vaginalis, and Pseudomonas aeruginosa. The agar dilution test was performed at concentrations ranging from 0.0001M to 0.7M of CSP. We obtained an effect of CSP antimicrobial, which was concentration-dependent. Concentrations low ( ≤ 0.007M) did not influence growth significantly. We observed partial growth inhibition at medium concentrations (0.05-0.07M, equivalent to approximately 780 -1092 µg/ml) of the solution. The growth of bacteria and yeasts was fully inhibited at 0.05M and 0.07M, respectively. The dose required to kill the organisms (not merely inhibit their growth) was 0.25M (approximately 2014 µg/ml) across all microorganisms used, and we verified this by observing no growth when samples were inoculated into fresh media. These findings have indicated that CSP possesses good antimicrobial efficacy against typical vaginal pathogens at doses that may be applied in topical therapies. However, some additional research is required, especially the research that will investigate the toxicity on human cells and the production of suitable formulations to be used clinically.